Drosophila melanogaster Chemosensory Pathways as Potential Targets to Curb the Insect Menace. - Ali, M.Z.; Anushree; Bilgrami, A.L.; Ahsan, J. (Insects, 2022)
From a unicellular bacterium to a more complex human, smell and taste form an integral part of the basic sensory system. In fruit flies Drosophila melanogaster, the behavioral responses to odorants and tastants are simple, though quite sensitive, and robust. They explain the organization and elementary functioning of the chemosensory system. Molecular and functional analyses of the receptors and other critical molecules involved in olfaction and gustation are not yet completely understood. Hence, a better understanding of chemosensory cue-dependent fruit flies, playing a major role in deciphering the host-seeking behavior of pathogen transmitting insect vectors (mosquitoes, sandflies, ticks) and crop pests (Drosophila suzukii, Queensland fruit fly), is needed. Using D. melanogaster as a model organism, the knowledge gained may be implemented to design new means of controlling insects as well as in analyzing current batches of insect and pest repellents. In this review, the complete mechanisms of olfactory and gustatory perception, along with their implementation in controlling the global threat of disease-transmitting insect vectors and crop-damaging pests, are explained in fruit flies.